Final answer:
The equivalent algebraic equation to solve the logarithmic equation log₃ (y +15) = log₃(y-5)+ log₃(5) is B. y + 15 = 5(y-5).
Step-by-step explanation:
To solve the given logarithmic equation, we can use the properties of logarithms. The equation log₃ (y +15) = log₃(y-5)+ log₃(5) can be simplified using the property that the log of a product is the sum of the logs. Therefore, we can combine the right side to get log₃ ((y-5)×5). This gives us log₃ (y +15) = log₃ (5y-25). Since the logs have the same base and are equal, their arguments must also be equal given that logarithmic functions are one-to-one. This simplifies to the algebraic equation y + 15 = 5(y-5), which is our answer B.